On the road to C(4) rice: advances and perspectives - Ermakova, Maria (Plant J, 2019)
The international C(4) rice consortium aims to introduce into rice a high capacity photosynthetic mechanism, the C(4) pathway, to increase yield. The C(4) pathway is characterised by a complex combination of biochemical and anatomical specialisation that ensures high CO(2) partial pressure at RuBisCO sites in bundle sheath (BS) cells. Here we report an update of the progress of the C(4) rice project. Since its inception in 2008 there has been an exponential growth in synthetic biology and molecular tools. Golden Gate cloning and synthetic promoter systems have facilitated gene building block approaches allowing multiple enzymes and metabolite transporters to be assembled and expressed from single gene constructs. Photosynthetic functionalisation of the BS in rice remains an important step and there has been some success overexpressing transcription factors in the cytokinin signalling network which influence chloroplast volume. The C(4) rice project has rejuvenated the research interest in C(4) photosynthesis. Comparative anatomical studies now point to critical features essential for the design. So far little attention has been paid to the energetics. C(4) photosynthesis has a greater ATP requirement, which is met by increased cyclic electron transport in BS cells. We hypothesise that changes in energy statues may drive this increased capacity for cyclic electron flow without the need for further modification. Although increasing vein density will ultimately be necessary for high efficiency C(4) rice, our modelling shows that small amounts of C(4) photosynthesis introduced around existing veins could already provide benefits of increased photosynthesis on the road to C(4) rice.